2016
DOI: 10.5572/ajae.2016.10.2.067
|View full text |Cite
|
Sign up to set email alerts
|

Predicting PM2.5 Concentrations Using Artificial Neural Networks and Markov Chain, a Case Study Karaj City

Abstract: The forecasting of air pollution is an important and popular topic in environmental engineering. Due to health impacts caused by unacceptable particulate matter (PM) levels, it has become one of the great est concerns in metropolitan cities like Karaj City in Iran. In this study, the concentration of PM 2.5 was predicted by applying a multilayer percepteron (MLP) neural network, a radial basis function (RBF) neural network and a Markov chain model. Two months of hourly data including temperature, NO, NO 2 , NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…An artificial neural network coupled with an atmospheric trajectory model reached an RMSE of 19.8 µg/m 3 for 1-day PM 2.5 forecasting and was very efficient at predicting the high peaks observable in the Jing-Jing-Ji area, China [50]. Better performance was found in a study performed in Iran that reached correlations of 0.86-0.91 and an RMSE of 2.76-7.04 µg/m 3 for hourly PM 2.5 forecast, however, these results were obtained by using PM 10 as a predictor variable for PM 2.5 forecasting [51]. While neural networks show impressive performances in predicting air quality at complex urban sites, their main limitation is that they can hardly be generalized for broader areas, and obtaining predictions for locations without measurements requires an atmospheric chemistry model or interpolation between sites.…”
Section: Discussionmentioning
confidence: 94%
“…An artificial neural network coupled with an atmospheric trajectory model reached an RMSE of 19.8 µg/m 3 for 1-day PM 2.5 forecasting and was very efficient at predicting the high peaks observable in the Jing-Jing-Ji area, China [50]. Better performance was found in a study performed in Iran that reached correlations of 0.86-0.91 and an RMSE of 2.76-7.04 µg/m 3 for hourly PM 2.5 forecast, however, these results were obtained by using PM 10 as a predictor variable for PM 2.5 forecasting [51]. While neural networks show impressive performances in predicting air quality at complex urban sites, their main limitation is that they can hardly be generalized for broader areas, and obtaining predictions for locations without measurements requires an atmospheric chemistry model or interpolation between sites.…”
Section: Discussionmentioning
confidence: 94%
“…It was reported by another research group that, using the WS, WD, and temperature as input variables, and ANN, AN-FIS models have provided SO 2 prediction with R 2 values between 0.20 and 0.50 [32], and in another study with R 2 >0.70 [33]. Recent research have proposed using both the meteorological factors and air pollutant parameters as input variables and reported that the ANN model produced a PM 2.5 prediction with R 2 >0.92 [34]. Another study revealed that the use of NO X and meteorological parameters as input variables and the ANFIS model provided O 3 predictions with R 2 >0.94 [35].…”
Section: The Prediction Approachmentioning
confidence: 99%
“…It has been employed in a wide range of applications such as modelling precipitation (da Silva et al, 2019 ; Schoof & Pryor, 2008 ), infrastructure deterioration (Baik et al, 2006 ), and wind speed (Sahin & Sen, 2001 ). Discrete-time Markov chains have also been employed to model air pollution (e.g., Asadollahfardi et al, 2016 ; Caraka et al, 2019 ; Mohamad et al, 2018 ; Romanof, 1982 ). Nebenzal and Fishbain ( 2018 ) found that, for forecasting long-term NO2 pollution, Markov chain models reduce the total error compared to other forecasting methods (e.g., multiple linear regression, moving average, exponential smoothing, Holt, and persistence methods).…”
Section: Introductionmentioning
confidence: 99%
“…Most air pollution studies that used Markov models focused on modelling specific contaminant concentrations such as particulate matter (Asadollahfardi et al, 2016 ; Caraka et al, 2019 ; Mohamad et al, 2018 ), nitrogen dioxide (Nebenzal & Fishbain, 2018 ), ozone (Rodrigues et al, 2019 ), and sulphur dioxide (Romanof, 1982 ), while few studies have focused on directly modelling an air pollution index similar to the AQHI (Alyousifi et al, 2018 ; Alyousifi et al, 2019 ; Zakaria et al, 2019 ). From a public health standpoint, directly modelling the AQHI is more informative since the AQHI categories are directly related to health risks and outdoor air quality advisories.…”
Section: Introductionmentioning
confidence: 99%